Advances in experimental social psychology. - Gawronski, Bertram (Issn., 2021)
The Advances in Experimental Social Psychology series is the premier outlet for reviews of mature, high-impact research programs in social psychology. Contributions to the series provide defining pieces of established research programs, reviewing and integrating thematically related findings by individual scholars or research groups. Topics discussed in Volume 64 include Moral Inference, Coalitional Cognition, Motivated Perception and Self-Regulation, Morality in Impression Development, and Self-Uncertainty and Group Identification.